Enhancing Children’s Self-Awareness in Diabetes Prevention through Digital Picture Books - Wardani, Lely Surya; Hendrawan, Faldi; Kabelen, Nicholaus Wayong (Journal of Visual Communication Design, 2026)
Childhood obesity persists as a significant global public health challenge, influenced not only by dietary factors but also by parental perceptions that frequently associate objectively overweight children with good health. This prevalent misconception can severely impede early prevention efforts and negatively impact children's physical and psychological development. This study aimed to develop and evaluate a digital picture book as an educational medium to enhance self-awareness among children aged 9–12 years concerning obesity prevention and the adoption of healthy lifestyles. Using a direct research method, data were systematically collected through structured interviews with parents, questionnaires administered to the target children, and direct observations during the intervention. The comprehensive evaluation specifically assessed children's understanding of health concepts, their engagement with the visual content, and their overall acceptance of the educational material. The developed digital picture book, titled "Aku Terlindungi dari Obesitas!" (I Am Protected from Obesity!), achieved a 'very good' effectiveness rating of 89% based on responses from 30 child participants in Malang City. These findings robustly indicate that the integrated visual and narrative approach effectively supports children's comprehension of obesity risks and actively promotes the adoption of healthy behaviors. This study significantly contributes to the field of visual communication design, demonstrating the potent capability of engaging visual storytelling in digital picture books to serve as an effective and accessible educational medium for the early prevention of childhood obesity.